Malaysia as cashless society: factor influencing the intention to adopt e-wallet among elderly - Pavithra, Janardhanan (2022)
Referring to the rapid growth of technology revolution around the globe, several nations are changing the financial transaction practices towards cashless approaches where electronic wallets are widely introduced their citizen including Malaysia. As a developing country, it is crucial for the stakeholder in Malaysia especially government, community, e-wallet services provider and so on to highly participate in term of assist nation to realize the goals to transforms nation become cashless society by technological approaches. Therefore, it is significant to examine the factors that influence the intention to adopt e-wallet in Malaysia especially among the elderly due the statistics showed less adoption among elderly. In this study, the main objectives derived are to analyses the relationship between perceived security, effort expectancy and performance expectancy with intention to adopt e-wallet among Malaysia elderly at the biggest state in Malaysia which is Pahang. Furthermore, instruments used for data collection is self-administered questionnaire which distributed to 384 respondents from the states chosen and data then is proceed for analysis by SPSS method.